Crucial role of polymeric binders in enhancing energy density of supercapacitors - Yoon, Juhee; Lee, Jeonghun; Yun, Young Soo; Kwak, Hyo won; Jin, Hyoung-Joon (Macromolecular research, 2025)
The growing demand for efficient energy storage solutions has driven significant advancements in supercapacitor technology, aimed at overcoming the traditional limitations of low energy density. This article reviews strategies for enhancing the energy density of supercapacitors, focusing on advancements in electrolyte formulations, activated carbon materials, pseudocapacitive materials, and binder technologies. Aqueous, ionic liquid, and organic electrolytes have been optimized to expand voltage windows and improve ionic conductivity, thereby increasing energy storage capacity. The development of high specific surface area carbon materials and the precise tailoring of pore size distributions have been shown to enhance capacitance. Pseudocapacitive materials, including metal oxides and MXenes, have demonstrated the potential for significantly higher energy densities through redox-active mechanisms. Innovations in binder systems, particularly those employing conductive materials like reduced graphene oxide, have further improved electrode performance by enhancing structural integrity and ion transport. A key focus is the role of polymer binders, which are vital for reducing the internal resistance and subsequent heat generation. Research in this area aims to develop binders that minimize resistive losses, improve ion transport efficiency, reduce heat generation and maintain optimal operating temperatures, prevent thermal degradation, and increase energy density. Continuous research into new materials and formulations for polymer binders is essential for advancing supercapacitor technology. Graphical abstract